Asset Management Decision-Making For Infrastructure Systems - Mohammadi, Alireza; Amador Jimenez, Luis.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook provides practical and concrete guidance for the step-by-step implementation of decision-making for infrastructure asset management. Examples are used to illustrate how data from condition assessment are used to develop performance models, to estimate the effectiveness of investments that are prioritized and scheduled to accomplish reliable and convenient infrastructure for the wellbeing of the public and regional economic competitiveness. Book illustrates numerous worked problems to clarify ambiguity in developing a decision-making platform to prioritize assets and distribute budgets effectively and efficiently. Ensures reader understanding of the benefits and challenges of infrastructure asset management; Provides a step-by-step guide for the development of each component of an asset management decision-making system; Includes worked examples to clarify decision-making and budget allocation process.
Introduction to Asset Management for Infrastructure -- Infrastructure Performance and Condition Assessment -- Future of Infrastructure -- Infrastructure Interventions -- Decision Support Systems for Infrastructure -- Emerging issues and new expectations.
Keywords: Facility management; Transportation engineering; Traffic engineering; Buildings Repair and reconstruction; Buildings Maintenance.; Engineering geology; Buildings Design and construction; Building laws; Facility Management; Transportation Technology and Traffic Engineering; Building Repair and Maintenance; Geoengineering; Building Construction and Design; Building Law for Engineers and Architects; Infrastructure (Economics) -- Decision making; Engineering -- Management